Polarization properties of the luminescence from silicon nanocrystals - Diener, J.; Kovalev, D.; Polisski, G.; Koch, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Polarization dependent photoluminescence (PL), time-resolved PL and PL excitation experiments are performed in order to clarify the origin of the linear polarization of the PL of porous silicon excited by linear polarized light. It is shown that this effect, when PL is excited significantly above the detection energy, is not related to a coherent exciton alignment or selective optical excitation of those nanocrystals whose transition dipole moments are oriented parallel to the polarization vector of the exciting light. The experimental results are interpreted in the framework of a dielectric model assuming aspheric nanocrystals.